A circulating cell population showing both M1 and M2 monocyte/macrophage surface markers characterizes systemic sclerosis patients with lung involvement - Amelia Chiara Trombetta; Stefano Soldano; Paola Contini; Veronica Tomatis; Barbara Ruaro; Sabrina Paolino; Renata Brizzolara; Paola Montagna; Alberto Sulli; Carmen Pizzorni; Vanessa Smith; Maurizio Cutolo (Respiratory Research, 2018)
Abstract Background Systemic sclerosis (SSc) is a disorder characterized by immune system alterations, vasculopathy and fibrosis. SSc-related interstitial lung disease (ILD) represents a common and early complication, being the leading cause of mortality. Monocytes/macrophages seem to have a key role in SSc-related ILD. Interestingly, the classically (M1) and alternatively (M2) activated monocyte/macrophage phenotype categorization is currently under revision. Our aim was to evaluate if circulating monocyte/macrophage phenotype could be used as biomarker for lung involvement in SSc. To this purpose we developed a wide phenotype characterization of circulating monocyte/macrophage subsets in SSc patients and we evaluated possible relations with lung involvement parameter values. Methods A single centre cross-sectional study was performed in fifty-five consecutive SSc patients, during the year 2017. All clinical and instrumental tests requested for SSc follow up and in particular, lung computed tomography (CT) scan, pulmonary function tests (PFTs), Doppler echocardiography with systolic pulmonary artery pressure (sPAP) measurement, blood pro-hormone of brain natriuretic peptide (pro-BNP) evaluation, were performed in each patient in a maximum one-month period. Flow cytometry characterization of circulating cells belonging to the monocyte/macrophage lineage was performed using specific M1 (CD80, CD86, TLR2 and TLR4) and M2 surface markers (CD204, CD163 and CD206). Non-parametric tests were used for statistical analysis. Results A higher percentage of circulating CD204+CD163+CD206+TLR4+CD80+CD86+ and CD14+CD206+CD163+CD204+TLR4+CD80+CD86+ mixed M1/M2 monocyte/macrophage subsets, was identified to characterize patients affected by SSc-related ILD and higher systolic pulmonary artery pressure. Mixed M1/M2 monocyte/macrophage subset showed higher percentages in patients positive for anti-topoisomerase antibody, a known lung involvement predictor. Conclusions The present study shows for the first time, through a wide flow cytometry surface marker analysis, that higher circulating mixed M1/M2 monocyte/macrophage cell percentages are associated with ILD, sPAP and anti-topoisomerase antibody positivity in SSc, opening the path for research on their possible role as pathogenic or biomarker elements for SSc lung involvement.